Desulphurization of Dibenzothiophene by Different Bacterial Strains: An Eco-Friendly Approach to Obtain Clean Fuel from Coal. Issue 6 (1st June 2022) - Kumar, Aniruddha; Singh, Asha Lata; Kumar, Rajesh; Rajak, Pramod K.; Singh, Prakash K.
Abstract: Coal is an important energy resource and many deposits contain a significant quantity of organic sulfur compounds. Combustion of coal releases SO2, CO2 and other gases into atmosphere and causes negative impact on the environment. Biodesulphurization of dibenzothiophene could be a prominent method for the removal of sulfur from coal. Here we successfully employed bacterial strains to degrade dibenzothiophene, and characterized through chromatography, high performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS). Strains of Ralstonia sp ., Pseudoxanthomons sp. and Rhodococcus sp. were used in the present investigation. Only Rhodococcus sp. converted dibenzothiophene (DBT) into 2-hydroxy biphenyl (2-HBP) and was able to additionally break the C-S bond without disturbing heterocyclic structure of DBT ring. This is also complemented by blue color of Gibb's assay which is indicative of DBT conversion into 2-HBP while brown color indicates complete consumption of DBT by bacteria. After two days of bacterial treatment, there was no further removal of DBT. DBT conversion into 2-HBP was monitored through HPLC during six days of experiment. Thus Rhodococcus sp. could be a proficient candidate for biodesulphurization of dibenzothiophene and eventually for biodesulphurizing organic sulfur rich coal with an eco-friendly and energy economical process. Though it is encouraging technique for desulphurization however more studies on coal are still required to support the industrial scale biodesulfurization.